Ventricular wall biomaterial injection therapy after myocardial infarction: Advances in material design, mechanistic insight and early clinical experiences. (June 2017) - Zhu, Yang; Matsumura, Yasumoto; Wagner, William R.
Abstract: Intramyocardial biomaterial injection therapy for myocardial infarction has made significant progress since concept initiation more than 10 years ago. The interim successes and progress in the first 5 years have been extensively reviewed. During the last 5 years, two phase II clinical trials have reported their long term follow up results and many additional biomaterial candidates have reached preclinical and clinical testing. Also in recent years deeper investigations into the mechanisms behind the beneficial effects associated with biomaterial injection therapy have been pursued, and a variety of process and material parameters have been evaluated for their impact on therapeutic outcomes. This review explores the advances made in this biomaterial-centered approach to ischemic cardiomyopathy and discusses potential future research directions as this therapy seeks to positively impact patients suffering from one of the world's most common sources of mortality.